2008
DOI: 10.1016/j.jvir.2008.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Different Methods for Inoculating VX2 Tumors in Rabbit Livers and Hind Limbs

Abstract: The authors recommend (a) the use of fresh VX2 cell suspension for percutaneous injection in the hind limbs of rabbits to maintain the VX2 cell strain and (b) the surgical implantation of freshly harvested VX2 tumor fragment into the liver parenchyma to establish liver tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 18 publications
1
47
0
7
Order By: Relevance
“…In terms of hepatic VX2 carcinoma model establishment, conventional surgical implantation of tumor fragments presents a higher success rate and a lower frequency of metastasis in comparison with the injection of tumor suspension cells (10). In the present study, the sizes of the hepatic allograft in each group were comparable, and the mean number of hepatic foci was 1.3-1.4, overcoming the aforementioned disadvantages of tumor suspension cell injection.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…In terms of hepatic VX2 carcinoma model establishment, conventional surgical implantation of tumor fragments presents a higher success rate and a lower frequency of metastasis in comparison with the injection of tumor suspension cells (10). In the present study, the sizes of the hepatic allograft in each group were comparable, and the mean number of hepatic foci was 1.3-1.4, overcoming the aforementioned disadvantages of tumor suspension cell injection.…”
Section: Discussionmentioning
confidence: 44%
“…Notably, the injection of tumor suspension cells is more likely to result in leakage and seeding of tumor cells, and has a decreased rate of successful model establishment, compared with the surgical implantation of tumor fragments (10,11). Conversely, Virmani et al (10) suggested that the injection of tumor suspension cells was recommendable. Nevertheless, the difficulties in determining the homogeneity of tumor suspension cell count, variations in the cell amount, and injection into small vessels of the liver result in a variation in tumor size and foci number, were also identified by Virmani et al (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial tumor development requires use of frozen VX2 sample, use of a fresh VX2 inoculum should be prioritized for subsequent tumor propagation. In a study by Virmani et al (21), inoculation of hind limb donor rabbits using fresh VX2 resulted in successful tumor growth in 88% of subjects, compared with 33% of subjects inoculated with frozen samples. Following inoculation, rabbits are monitored for appetite.…”
Section: Vx2 Hind Limb Tumor Developmentmentioning
confidence: 99%
“…Liver tumor implantation via laparotomy Intrahepatic implantation of solid tumor fragments is more reliable than the injection of a cell suspension. In a study by Virmani et al (21), solid tumor implantation and injection of cell suspension were associated with success rates of 84% and 43%, respectively, as determined by evidence of tumor growth on magnetic resonance imaging and subsequent histopathological analysis. In a report by Chen et al (22), implantation was successful in 95% of cases and injection in 35% of cases, and the latter was associated with a high rate of extrahepatic tumor growth.…”
Section: Vx2 Hind Limb Tumor Growth and Harvestingmentioning
confidence: 99%